2020
DOI: 10.1016/j.mehy.2020.110151
|View full text |Cite
|
Sign up to set email alerts
|

Why do children seem to be more protected against COVID-19? A hypothesis

Abstract: Today it remains unclear why children seem to be less likely to get infected by COVID-19 or why they appear to be less symptomatic after infections. All individuals, especially children, are exposed to various viruses including human coronavirus (CoVs) that can generally lead to respiratory infections. We hypothesize that recurrent CoVs exposure may induce an effective antiviral B and T-cell-mediated adaptive immune response, which could also be protective against COVID-19. Based on the high-homology between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…These age-dependent differences in disease expression and severity have clear implications for healthcare professionals who deal with the pediatric population because children remain at risk for incurring and spreading the virus, yet many remain asymptomatic. Several hypotheses have been posited as to why children are less affected by COVID-19, including age-related differences in immune responses [16], a neutralizing antibody response due to prior exposure to coronaviruses [17], lower prevalence of co-morbidities in children, and age-specific differences in SARS-CoV-2 receptor function [18], neurovirulence, intrinsic biological protective mechanisms, and other host factors [19]. None of these hypotheses is supported compellingly by extant data at present.…”
Section: Covid-19 In Neonates and Childrenmentioning
confidence: 99%
“…These age-dependent differences in disease expression and severity have clear implications for healthcare professionals who deal with the pediatric population because children remain at risk for incurring and spreading the virus, yet many remain asymptomatic. Several hypotheses have been posited as to why children are less affected by COVID-19, including age-related differences in immune responses [16], a neutralizing antibody response due to prior exposure to coronaviruses [17], lower prevalence of co-morbidities in children, and age-specific differences in SARS-CoV-2 receptor function [18], neurovirulence, intrinsic biological protective mechanisms, and other host factors [19]. None of these hypotheses is supported compellingly by extant data at present.…”
Section: Covid-19 In Neonates and Childrenmentioning
confidence: 99%
“…Furthermore, there are significantly fewer pediatric patients with COVID‐19, compared with adult patients 15,16 . This is presumably because children have had fewer environmental exposures to SARS‐CoV‐2 12,17 . However, pediatric patients may not undergo laboratory tests because they exhibit few or no symptoms, thus, there are relatively few laboratory confirmed cases 2,12,18‐20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, pediatric patients may not undergo laboratory tests because they exhibit few or no symptoms, thus, there are relatively few laboratory confirmed cases 2,12,18‐20 . Some epidemiological studies have indicated out that SARS‐CoV‐2 susceptibility and spread characteristics are less robust in children than in adults 17,21,22 . To the best of our knowledge, there have been few evidence‐based reports concerning pediatric susceptibility to SARS‐CoV‐2.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, ожидаемый внутриклеточный ответ, индуцированный ACE2, в альвеолярных эпителиальных клетках детей ниже, чем у взрослых. В соответствии с этим становятся понятны причины более высокой чувствительности к SARS-CoV-2 у детей верхних дыхательных путей, чем нижних [1,14].…”
Section: особенности патофизиологии Covid-19 у детейunclassified